ANALISIS PERAN DEWAN PENGAWAS SYARIAH DALAM PERBANKAN SYARIAH - Oktaviany, Mega; Rizky, Muhammad; Putri, Siti Nabila; Azhari, Zulfa Maula (Taksasila Edukasi Insani, 2025)
The Sharia Supervisory Board (DPS) plays a crucial role in ensuring that Islamic banks operate in accordance with Sharia principles. The main functions of DPS include issuing fatwas, approving products, and supervising the implementation of Islamic banking products to ensure they are free from elements of riba, gharar, and maysir. DPS also ensures that every product launched by an Islamic bank complies with Islamic law and does not harm customers or other parties. Although the role of DPS is essential, challenges in Sharia supervision include limited resources, the influence of globalization, and the uneven understanding of Sharia principles among bank management. Best practices in Sharia supervision involve close collaboration between DPS, bank management, and the implementation of adequate information technology to enhance the effectiveness of supervision. Several successful Islamic banks, such as Islami Bank Bangladesh Limited and Bank Islam Brunei Darussalam, have demonstrated that the synergy between DPS and management, along with the adoption of technology, can improve the quality of supervision and the development of Sharia-compliant products. Therefore, it is recommended that DPS continue to enhance its capacity, strengthen collaboration with management, adopt information technology to support more effective supervision, and adapt to globalization and international regulations. Keywords : Sharia Supervisory Board, Islamic banking, Sharia compliance, supervision, information technology